I was writing out the proof of $\sin’x=\cos x$ and ended up with something that was wrong, but I’m not sure why. Here it is: enter image description here

  • 2
    $\begingroup$ For a general $x$, for instance for $x=\pi/4$, $$\frac{\sin x}h$$ has no limit for $h\to 0$, so the first split makes no sense. $\endgroup$ – dan_fulea Oct 1 '18 at 17:31
  • 1
    $\begingroup$ How you jumped from 3rd line to 4th? you will have a term of $\cos{x}$, as, $\lim_{h\to 0}\frac{\sin{h}}{h}=1$ $\endgroup$ – tarit goswami Oct 1 '18 at 17:31
  • 7
    $\begingroup$ So $\infty-\infty=0?\ \ddot\frown$ $\endgroup$ – Lord Shark the Unknown Oct 1 '18 at 17:32
  • 4
    $\begingroup$ Instead of splitting the fractions the way you did, try $$\frac{\sin(x)(\cos(h) - 1)}{h} + \frac{\sin(h)\cos(x)}{h}$$ $\endgroup$ – Bungo Oct 1 '18 at 17:36

You broke up the initial limit incorrectly. The correct proof would be like this. (Notice how the limit is split up.) $$\sin’x = \lim_{h\to 0}\big(\frac{\sin(x+h)-sin(x)}{h}\big)$$ $$=\lim_{h\to 0}\big(\frac{\sin x\cos h+\cos x\sin h-\sin x}{h}\big)$$ $$=\lim_{h\to 0}\big(\frac{\sin x\cos h- \sin x+\cos x\sin h}{h}\big)$$ $$=\lim_{h\to 0}\big(\frac{\sin x(\cos h-1)+\cos x\sin h}{h}\big)$$ $$=\lim_{h\to 0}\big(\frac{\sin x(\cos h-1)}{h}+\frac{\cos x\sin h}{h}\big)$$ $$=\lim_{h\to 0}\frac{\sin x(\cos h-1)}{h}+\lim_{h\to 0}\frac{\cos x\sin h}{h}$$ $$=\sin x\cdot\lim_{h\to 0}\frac{\cos h-1}{h}+\cos x\cdot\lim_{h\to 0}\frac{\sin h}{h}$$ $$=\sin x\cdot 0 + \cos x\cdot 1 = \cos x$$ $$\implies \boxed{\sin’x = \cos x}$$


In the second to last line, both limits don't exist. Akin to $\infty-\infty \neq 0$


You have no reason to simplify

$$\frac{\sin x\cos h+\cos x\sin h}{h}$$ in $$\frac{\sin x}h.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.